Outcomes of Acellular Dermal Matrix for Immediate Tissue Expander Reconstruction with Radiotherapy: A Retrospective Cohort Study. (24th May 2018) - Craig, Elizabeth S; Clemens, Mark W; Koshy, John C; Wren, James; Hong, Zhang; Butler, Charles E; Garvey, Patrick B; Selber, Jesse C; Kronowitz, Steven J
Abstract: Background: Despite increasing literature support for the use of acellular dermal matrix (ADM) in expander-based breast reconstruction, the effect of ADM on clinical outcomes in the presence of post-mastectomy radiation therapy (PMRT) has not been well described. Objectives: To analyze the impact ADM plays on clinical outcomes on immediate tissue expander (ITE) reconstruction undergoing PMRT. Methods: We retrospectively reviewed patients who underwent ITE breast reconstruction from 2004 to 2014 at MD Anderson Cancer Center. Patients were categorized into four cohorts: ADM, ADM with PMRT, non-ADM, and non-ADM with PMRT. Outcomes and complications were compared among cohorts. Results: Over 10 years, 957 patients underwent ITE reconstruction (683 non-ADM, 113 non-ADM with PMRT, 486 ADM, and 88 ADM with PMRT) with 1370 reconstructions. Overall complication rates for the ADM and non-ADM cohorts were 39.0% and 16.7%, respectively ( P < 0.001). Within both cohorts, mastectomy skin flap necrosis (MSFN) was the most common complication, followed by infection. ADM use was associated with a significantly higher rate of infections and seromas in both radiated and non-radiated groups; however, when comparing radiated cohorts, the incidence of explantation was significantly lower with the use of ADM. Conclusions: The decision to use ADM for expander-based breast reconstruction should be performed with caution, given higher overall rates of complications, including infections and seromas. There may, however, be a role for ADM in cases requiring PMRT, as the overall incidence of implant failure is lower than non-ADM cases. Level of Evidence: 3: